2013
DOI: 10.1021/jp409586z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Photon Energy and Semiconductor Substrate in the Plasmon-Mediated Photooxidation of Citrate by Silver Nanoparticles

Abstract: The plasmon-mediated photooxidation of citrate ions adsorbed on silver (Ag) nanoparticle−semiconductor electrodes is studied in a photoelectrochemical cell. Consistent with previous reports, a negative photovoltage and an anodic photocurrent arise from citrate photooxidation under weak visible light illumination. We measure the wavelength dependence of this reaction for three different types of Ag nanoparticles and find that both the photovoltage and photocurrent increase with photon energy over the visible sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 69 publications
10
89
0
Order By: Relevance
“…It is noteworthy that the smaller AgNPs are capped with the lower molecular weight ligands with the carboxylate-to-alcohol ratio of 1, which, therefore, form, possibly via radical reactions [41,42], at early stages of the process, arresting the crystal growth ( Figure 5, b). The mechanisms need further study, but, anyway, the reactions are different from those in the solution bulk or living cell mitochondria, which proceed via the stages of oxidation of alcohol group to ketone as an intermediate, dehydration and decarboxylation [13,[26][27][28][29]. Conversely, no ketones were found at all the Ag surfaces, and no surface C=O groups have been revealed with in situ SERS for the iron-free media too [9,10], probably because of stabilization of alcohol group bound to silver.…”
Section: Origin Of the Citrate-derived Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the smaller AgNPs are capped with the lower molecular weight ligands with the carboxylate-to-alcohol ratio of 1, which, therefore, form, possibly via radical reactions [41,42], at early stages of the process, arresting the crystal growth ( Figure 5, b). The mechanisms need further study, but, anyway, the reactions are different from those in the solution bulk or living cell mitochondria, which proceed via the stages of oxidation of alcohol group to ketone as an intermediate, dehydration and decarboxylation [13,[26][27][28][29]. Conversely, no ketones were found at all the Ag surfaces, and no surface C=O groups have been revealed with in situ SERS for the iron-free media too [9,10], probably because of stabilization of alcohol group bound to silver.…”
Section: Origin Of the Citrate-derived Ligandsmentioning
confidence: 99%
“…Сitrate is a key reagent for the preparation of silver nanoplates, cubes, disks, etc., as the selective adsorption of citrate on Ag (111) facets impedes their growth and promotes the yield of anisotropic particles [12,[23][24][25]. Transformation of rounded AgNPs to anisotropic ones under illumination [26][27][28] is believed to be due to decomposition of the citrate capping.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, when the in-plane dipole resonance is excited, ''hot'' electrons and ''hot'' holes are generated and concentrated at surfaces on the nanoparticle in the same plane as the dipole excitation. At these surfaces, ''hot'' holes oxidize surface-bound citrate molecules into 1,3-acetonedicarboxylate and carbon dioxide though the photo-Kolbe mechanism, where the hydroxyl group of sodium citrate donates an electron pair to the central carbon atom forming a carbon-oxygen double bond which subsequently causes the central carbon to undergo heterolytic cleavage with the rest of the citrate molecule thereby releasing carbon dioxide [23]. NMR studies have previously shown supporting evidence of emerging 1,3-acetonedicarboxylate, with a corresponding peak at d = 3.49 ppm, upon photoexcitation of the silver nanospheres into triangular nanoprisms [24].…”
Section: Introductionmentioning
confidence: 99%
“…This subsequently reduces Ag ? ions in solution to Ag 0 resulting in selective in-plane growth [23][24][25]. Triangular nanoprisms are found to have a maximuminduced electromagnetic field localized at the tips from electron energy loss spectroscopy (EELS) when their inplane SPR is excited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metal nanoparticles can absorb light much more efficiently when compared to semiconductors and dye molecules. Therefore, the use of photo-excited plasmonic electrons is potentially very attractive for applications in photochemistry and photo-catalysis [24][25][26][27][28][29][30][31][32], solar energy harvesting (solar cells) [8][9][10][11][12]20,33,34] and optoelectronics [23,[35][36][37][38][39]. For example, in their work,…”
Section: Introductionmentioning
confidence: 99%